Territorialized Commons and Social Movements: Legal Appropriations of Collective Spaces in Berlin and Santiago de Chile - Amacher, David; Kip, Markus; Opazo, Daniel (Frontiers in Sustainable Cities, 2022)
This article aims to explore the relationship between territorialized commons and movements and how the use of legal strategies of appropriation mediates this relationship. We study two recent commoning practices for collective space in Berlin and Santiago de Chile that have appropriated publicly owned land for their initiative, engaging with legal institutions to meet the ends of the movement. This type of relationship to movements has not been given serious consideration in the commons literature and we ask how these commoning initiatives make the appropriated land a common resource for the movement and resist privatization. Based on secondary sources and interviews with activists, we conclude that both initiatives in Berlin and Santiago de Chile have drawn on legal frameworks for transformative purposes while also politicizing the question of public land as an asset for civic and commoning use. However, said frameworks do not replace activist engagement and self-organization as the main element behind commoning processes.